Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus